Pressure, Dysfunctional Behavior, Fraud Detection and Role of Information Technology in the Audit Process - Muhammad Umar; Shinta Megawati Sitorus; Rika Lusiana Surya; Elvia R. Shauki; Vera Diyanti (Australasian Accounting, Business and Finance Journal, 2017)
This study examines the effect of information technology and pressure such as time budget and task complexity on dysfunctional audit behavior. This study tests whether dysfunctional audit behavior affects fraud detection. Data were gathered from 81 auditors in Jakarta and were analyzed using structure equation model (SEM). The results explain that pressure (time budget and complexity task) have some impacts on dysfunctional audit behavior while information technology does not affect dysfunctional audit behavior. These results also indicate that dysfunctional audit behavior has an adverse effect on fraud detection. Job-related stress framework explains the conditions that make stress (stressors) will affect to individual psychology, physics, and behavior (strains) and make some result (outcome). Pressure (time budget and complexity task) is the condition that makes both positive and negative effect on individual behavior. Pressure can make individuals behave dysfunctional or motivate them to give their best shot even though their work uses a lot of energy and mind to solve the problems. Raising dysfunctional audit behavior will reduce auditor’s ability to identify material misstatement in the financial statement.
Keywords: Dysfunctional audit behavior; fraud detection; information technology; task complexity; and time budget pressure; Indonesia.